Impact of obesity on incision to delivery interval and neonatal outcomes at cesarean - CONNER, Shayna N. (2013)
OBJECTIVE: To test the hypothesis that increasing body mass index (BMI) is associated with increased time from skin incision to infant delivery and increased neonatal morbidity at cesarean. STUDY DESIGN: We performed a retrospective cohort study of all cesarean deliveries occurring at one institution from 2004-2008. Four comparison groups were defined by body mass index (BMI) <30 kg/cm2 (n=668), 30-39.9 (n=1002), 40-49.9 (n=403), or ≥50 (n=193). The primary outcome was time from skin incision to infant delivery. Secondary outcomes were a composite measure of neonatal morbidity and its individual components: 5-minute Apgar score less than 7, umbilical cord arterial pH <7.10 and <7.20, umbilical cord arterial base excess <-8 (mmol/L), Special Care Nursery (SCN) admission, and NICU admission. RESULTS: Increasing BMI was associated with significantly increased time from skin incision to infant delivery, demonstrating a dose response pattern. Minutes from skin incision to delivery of the infant by BMI strata were; 9.4 ± 5.9 for BMI <30, 11.0 ± 6.8 for BMI 30-39.9, 13.0 ± 8.0 for BMI 40-49.9, and 16.0 ± 11.3 for BMI ≥50 (p < 0.01). Composite neonatal morbidity was significantly higher with increasing BMI; 23.0% for BMI <30, 25% for BMI 30-39.9, 29.8% for BMI 40-49.9, and 32.1% for BMI ≥ 50 (p=0.02). CONCLUSION: Increasing BMI is associated with a significantly increased time from skin incision to infant delivery and neonatal morbidity. Cesarean technique remains to be optimized for obese women.